The Influence of Problem Based Learning Models on Students' Critical Thinking Ability on Natural Disaster Mitigation Material - Abdullah, Irwan; Ningrum, Epon (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
Critical thinking is an essential skill in 21st century society. The condition of students' critical thinking skills is the basis of implementation Problem Based Learning (PBL) in geography class. This study aims to determine the level of Influence of the PBL on Students' Critical Thinking Skills on Natural Disaster Mitigation material. This research used a quasi-experimental method with a non-equivalent control group design, which is a design consisting of two groups, namely the experimental and control groups. Sampling technique was purpossively, consisting of 13 experimental class students and 12 control class students. The data collection technique involves written essay tests in both pretest and posttest. The data has been analyzed quantitatively. The research results indicate that, descriptively, students in the PBL group achieved higher average scores in critical thinking skills compared to those in conventional learning. Furthermore, a significant difference exists in critical thinking skills between the PBL group and conventional learning, with PBL demonstrating a significant impact on students' critical thinking skills. It is better if the PBL is given by teachers to improve students' critical thinking skills.